Multimodal individual emotion recognition with joint labeling based on integrated learning and clustering - KE Shanjun; NIE Chengyang; WANG Yumiao; HE Bangsheng (智能科学与技术学报)
To address the low recognition accuracy of generic emotion recognition models when faced with different individuals, a multimodal individual emotion recognition technique based on joint labelling with integrated learning and clustering was proposed. The method first trained a generic emotion recognition model based on a public dataset, then anallysed the distributional differences between the data in the public dataset and the unlabelled data of individuals, and established a cross-domain model for predicting and labelling pseudo-labels of individual data. At the same time, the individual data were weighted clustered and labelled with cluster labels, and the cluster labels were used to jointly label with pseudo-labels, and high confidence samples were screened to further train the generic model to obtain a personalized emotion recognition model. Using this method to annotate these data with the experimentally collected data of 3 emotions from 3 subjects, the final optimized personalized model achieved an average recognition accuracy of more than 80% for the 3 emotions, which was at least a 35% improvement compared to the original generic model.